Person-Job Fit and Psychological Meaningfullness as A Predictor of Work Engagement In Call Center Employees PT. X - Ressy Mardiyanti; Berliana Nur Chafsah; Diandra Maharani (Psikostudia : Jurnal Psikologi, 2023)
The rate of turnover for employees in a company will be of particular concern because it involves the company's expenses which are not cheap. When recruiting employees, it is hoped that individuals will be compatible with their jobs, and this compatibility will make employees psychologically meaningful at work and be able to immerse themselves in or be attached to their work, so that employees can last a long time in the company and reduce the budget for the recruitment, selection, and training processes. This study aims to determine the effect of Person Job Fit and Psychological meaningfulness in looking at work engagement in employees. The subject is a call center employee of PT. X aged 20-45 years. This research uses quantitative methods, uses a measuring instrument with a questionnaire model on the variable person job fit, psychological meaningfullness and work engagement. The results of this study indicate that Person Job Fit and psychological meaningfulness affect work engagement in call center employees at PT. X. Variable Person Job Fit and psychological meaningfulness together contribute 71% to work engagement. There needs to be matching between individuals and jobs at the beginning, to reduce the turnover of employees.Laju keluar-masuk karyawan pada suatu perusahaan akan menjadi perhatian khusus, karena menyangkut pengeluaran biaya perusahaan yang tidak sedikit. Saat penerimaan karyawan diharapkan individu memiliki kecocokan dengan pekerjaannya, dan kecocokan itu membuat karyawan memiliki makna secara psikologi dalam bekerja dan mampu tenggelam atau memiliki keterikatan dengan pekerjaannya, sehingga karyawan pun dapat bertahan lama diperusahaan dan menekan anggaran proses rekrutmen, seleksi serta training. Penelitian ini bertujuan untuk mengetahui pengaruh dari Person Job Fit, Psychological meaningfulness dalam melihat work engagement pada karyawan. Subjek merupakan karyawan call center PT. X yang berusia 20-45 tahun. penelitian ini menggunakan metode kuantitatif, menggunakan alat ukur dengan model kuisioner pada variabel person job fit, psychological meaningfullness dan work engagement. Hasil penelitian ini menunjukkan bahwa Person Job Fit dan psychological meaningfulness mempengaruhi work engagement pada karyawan call center PT. X. Variable Person Job Fit dan psychological meaningfulness secara bersama-sama memberikan kontribusi pengaruh sebesar 71% terhadap work engagement. Perlu adanya pencocokan antara individu dengan pekerjaan diawal, untuk menekan keluar-masukknya karyawan.